23 seats go to Pro Mahasiswa - New Straits Times, Hanis Maketab dan Azlee Nor Mahmud
Kuala Lumpur: Pro Mahasiswa emerged the winner in the University of Malaya students Representive Council (MPPUM)election yesterday.